Removal of Cr(VI) from aqueous solutions by nZVI-loaded sludge-derived biochar performance and mechanism - Yu, Chaoyang (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
With the rapid development of highland railways in China, a large amount of heavy metal wastewater was inevitably generated during the manufacturing process of alloy materials required for railway construction. In this paper, pyrolysis of municipal sludge was followed by ball milling to obtain ball milling sludge-derived biochar (SDBC), and then nZVI-loaded SDBC materials (nZVISDBC) were prepared by liquid-phase reduction. The effects of different factors on the Cr(VI) removal were investigated. The maximum Cr(VI) adsorption capacity of nZVI@SDBC(2:1) was 178.05 mg/g. The Cr(VI) removal process could be fitted by the Langmuir isotherm and pseudo-second-order kinetic model. The Cr(VI) removal mechanism mainly included complexation, reduction, electrostatic interaction, and coprecipitation. The Cr(VI) removal by nZVI@SDBC(2:1) was maintained at over 90% after five replicate experiments. nZVI@SDBC(2:1) was capable of removing most of the Cr(VI) from real electroplating wastewater. The cost of using nZVI@SDBC(2:1) to remove 1 m3 of actual wastewater is approximately 325.7162 USD/m3. This work provided a new idea for the solution of Cr(VI)-containing wastewater from the production of railway materials